Application of gaseous chlorine dioxide for control of fungal fruit rot disease of harvested ‘Daw’ longan - Nitiya Guntiya (2018)
© 2016 Elsevier B.V. Longan (Dimocarpus longan Lour.) fruit decay caused by microbial infection during storage is the main problem that results in a great loss of its market value. The objective of this study was to investigate the application of gaseous chlorine dioxide (ClO2) to control fruit rot disease caused by three fungi: Cladosporium sp., Fusarium sp., and Lasiodiplodia sp. in longan fruit. The effect of ClO2fumigation at 10 mg L-1for 10 min on the onset of disease and the activities of two defense enzymes, chitinase and glucanase, in the harvested longan fruits during storage at 25 ± 3 °C for 7 days were investigated. The inhibition of fungal growth and spore germination, and oxidative damage to fungal membrane by gaseous ClO2were also studied. It was found that ClO2fumigation could significantly reduce disease incidence (by 20–75%) and disease index (by 28–38%) of the inoculated longans and markedly increased chitinase and glucanase activities during 7 days of storage. ClO2stimulated the activity of chitinase and glucanase which were increased by 29.45–58.89% and 68.98–78.12%, respectively higher than those in the inoculated controls. ClO2was more efficient in stimulating the activity of glucanase than that of chitinase. ClO2also increased fungal membrane damage by causing an increase in malondialdehyde and conjugated diene contents, lipoxygenase activity and electrolyte leakage. The increase in the activities of both enzymes in fruits and the increase in fungal membrane damage causes by ClO2, were in accordance with the inhibition of fungal growth and spore germination, leading to the reduction of fruit rot disease suggesting that it is the response mechanism of longan to reduce fungal fruit rot caused by the pathogens.